2022
DOI: 10.3390/bios12030174
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O-Based Electrochemical Biosensor for Non-Invasive and Portable Glucose Detection

Abstract: Electrochemical voltammetric sensors are some of the most promising types of sensors for monitoring various physiological analytes due to their implementation as non-invasive and portable devices. Advantages in reduced analysis time, cost-effectiveness, selective sensing, and simple techniques with low-powered circuits distinguish voltammetric sensors from other methods. In this work, we developed a Cu2O-based non-enzymatic portable glucose sensor on a graphene paste printed on cellulose cloth. The electron tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It has been proposed that the HCHO oxidation reaction plays a key role in enhancing the electron transfer efficiency of the Cu(III) reduction and Cu(II)/Cu(I) transition accordingly. , Therefore, we proposed the mechanism of HCHO sensing based on bio-electrocatalytic activity of ALDH and Cu electrodes could be described as follows 2 normalC normalu normalI normalI normalI normalO normalO normalH + normalH normalC normalH normalO + normalH 2 normalO true normalA normalL normalD normalH 2 normalC normalu normalI normalI false( normalO normalH false) 2 + normalH normalC normalO normalO normalH …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that the HCHO oxidation reaction plays a key role in enhancing the electron transfer efficiency of the Cu(III) reduction and Cu(II)/Cu(I) transition accordingly. , Therefore, we proposed the mechanism of HCHO sensing based on bio-electrocatalytic activity of ALDH and Cu electrodes could be described as follows 2 normalC normalu normalI normalI normalI normalO normalO normalH + normalH normalC normalH normalO + normalH 2 normalO true normalA normalL normalD normalH 2 normalC normalu normalI normalI false( normalO normalH false) 2 + normalH normalC normalO normalO normalH …”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the HCHO oxidation reaction plays a key role in enhancing the electron transfer efficiency of the Cu­(III) reduction and Cu­(II)/Cu­(I) transition accordingly. , Therefore, we proposed the mechanism of HCHO sensing based on bio-electrocatalytic activity of ALDH and Cu electrodes could be described as follows …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One more technology for the fabrication of copper oxide-based biosensors for non-invasive glucose detection was developed recently by Franco et al 173 In order to fabricate the sensor, the authors first print-coated electrodes onto fabric that was made of cellulose using a paste containing graphene. Cellulose is an excellent substrate material as it offers an attractive combination of minimal cost and toxicity, abundance, excellent compatibility with living systems, the ability to be disposed of and degrade naturally, as well as excellent porosity that maximises the contact area between the sensor and the biofluid.…”
Section: Innovations In the Application Of Cuo Nanowire-based Metamat...mentioning
confidence: 99%
“…Considering the high stability of copper oxide than copper NCs, investigation in this field can open a new landscape to fill the gaps correlated to low stability and reduced optical properties of copper NCs, especially in biological fluids where various types of small and macromolecules can reduce their resistance and emission properties. Cu 2 O-based nanoparticles are popularly employed as electrosensitizers in electrochemical, ECL, and PEC point-of-care systems. ,, Yin et al reported the application of Cu/Cu 2 O NCs for glucose sensing. In this strategy, Cu/Cu 2 O NCs are employed as an electrocatalyst to enhance the oxidation rate of glucose, leading to increased current and then the detection sensitivity using the amperometry technique.…”
Section: Nonmetallic Ncsmentioning
confidence: 99%